Respuesta :
The answer is - [tex] \frac{1}{2} [/tex]
Given: y = sin(x) cos(x)
Applying the product rule of differentiation, we get,
[tex] \frac{dy}{dx} [/tex]= sin(x) . [tex] \frac{dy}{dx} [/tex] cos(x) + cos(x)[tex] \frac{dy}{dx} [/tex] sin(x)
= sin(x) × -sin(x) + cos(x)cos(x)
= - sin²x + cos²x
= - sin²x + (1- sin²x)
= 1 - 2sin²x = cos 2x
Now, we need to find, [tex] \frac{dy}{dx} at x = \frac{π}{3} [/tex]
[tex] \frac{dy}{dx} [/tex] = cos (2×60) = cos (120)
⇒[tex] \frac{dy}{dx} = - \frac{1}{2} [/tex]
Given: y = sin(x) cos(x)
Applying the product rule of differentiation, we get,
[tex] \frac{dy}{dx} [/tex]= sin(x) . [tex] \frac{dy}{dx} [/tex] cos(x) + cos(x)[tex] \frac{dy}{dx} [/tex] sin(x)
= sin(x) × -sin(x) + cos(x)cos(x)
= - sin²x + cos²x
= - sin²x + (1- sin²x)
= 1 - 2sin²x = cos 2x
Now, we need to find, [tex] \frac{dy}{dx} at x = \frac{π}{3} [/tex]
[tex] \frac{dy}{dx} [/tex] = cos (2×60) = cos (120)
⇒[tex] \frac{dy}{dx} = - \frac{1}{2} [/tex]
The value of [tex]dy/dx[/tex] at [tex]x=\pi/3[/tex] is (-1/2).
Step-by-step explanation:
Given information:
The expression [tex]y=sinx.cosx[/tex]
And [tex]x= \pi/3[/tex]
Now to find derivative [tex]dy/dx[/tex] of the given expression
Apply product rule for differentiation :
As,
[tex]y=sinx.cosx\\\\\frac{dy}{dx} = (sinx .\frac{dy}{dx}cosx)+ (cosx.\frac{dy}{dx}sinx)\\\\\frac{dy}{dx}=(sinx.(-sinx))+(cosx.cosx)\\\\\frac{dy}{dx}=-sin^2x+cos^2x\\\\\frac{dy}{dx} =-sin^2x+(1-sin^2x)\\\\\frac{dy}{dx}=1-2sin^2x\\\\\frac{dy}{dx}=cos2x\\[/tex]
Now , at [tex]x= \pi/3[/tex]
[tex]dy/dx=cos2x\\dy/dx=cos(2 \times 60)\\dy/dx=cos120\\dy/dx=(-1/2)[/tex]
Hence , the value of [tex]dy/dx[/tex] at [tex]x=\pi/3[/tex] is (-1/2).
For more information visit:
https://brainly.com/question/24235106?referrer=searchResults